Games based learning in mathematics education: A systematic literature review - Dika Faiz Himmawan; Dadang Juandi (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
This study aims to describe and evaluate the effects of game-based mathematics learning. Systematic Literature Review (SLR) is used as a method in this research by collecting primary studies through checking the Google Scholar database, Education Resources Information Center (ERIC) from 2013 to 2022 with the keywords "games and learning mathematics" or "games and mathematics education", resulting in 25 relevant primary studies with inclusion criteria. The analysis technique used for the articles or primary studies that have been collected is that each primary study is recorded, then classified by title and year of study. Furthermore, each of the articles included in this study was analyzed to obtain the findings and discussion required to draw conclusions from this SLR study. It shows several results from the 25 articles used as material for the analysis of game-based mathematics learning, namely: 1) There are two types of games that are applied in the process of learning mathematics, namely traditional games, and modern games. 2) In general, the influence of the application of games, both traditional and modern, on learning mathematics is to improve the quality of learning with better indicators of teacher skills and student activity. From the results of this analysis, it can be concluded that the application of games in the process of learning mathematics is effective, because it affects the quality of learning mathematics in schools, especially by increasing student competence. The findings of this study also contribute to providing information related to the trend of game-based mathematics learning in Indonesia, which is expected to become recommendations and ideas for further research.